Evaluación del efecto de la adición de un microencapsulado de extracto de tzintzo (Tagetes minuta) en el retardo de la oxidación lipídica de un queso crema durante su almacenamiento acelerado. - Dias Cunuhay, Nelson Gustavo (2023)
In the current research, it was made with the aim by assessing a microencapsulated extract addition effect from tzintzo (Tagetes minuta) into cream cheese, which was elaborated three samples: a base as an indicator sample and two with different concentrations from microencapsulated (minimum 0,02% and maximum 0,04%); the fatty acids presence into this product allowed to determine the lipid oxidation retardation with the characterization, through the analysis of peroxide and acidity index; for 21 days under an accelerated storage method at three different temperatures (25, 35 and 45 ºC). Given as result ascending values for the three treatments; at 25 ºC the indicator sample (MI), started with a 0,40 meqO2/kg peroxide index (IP) until it reached 1,07 meqO2/kg, sample A (MA) increased from 0,67 to 1,87 meqO2/kg and sample B (MB) had a variation into its peroxide index from 1,47 to 4,27 meqO2/kg. On the other hand, at 35 ºC 1,47, it was reached meqO2/kg values into MI, for the MA it was had 2,20 meqO2/kg and for MB 5,80 meqO2/kg. Also, at 45 °C, was reached 2,47 meqO2/kg values into MI, for MA it was had 3,20 meqO2/kg and into MB 6,80 meqO2/kg. Regarding the acidity index at 25 ºC, the MI treatment went from 0,65 to 1,21 % m/m of lactic acid, MA began with 0,62 and ended with 1,63 % m/m and MB reached 0,17 at 1,22 % m/m. On storage at 35 ºC MI was finished with 1,39 % m/m, MA with 1,63 % m/m and MB with 1,22 % m/m. While in the storage at 45 °C the MI ended with 1,51 % m/m, MA with 1,72 % m/m and MB with 1,31 % m/m. For cream cheese shelf life determining, through the food degradation kinetics model, it was shown, what the best treatment was the MA sample (0,02% microencapsulated), reflecting the antioxidant action or capacity, estimating a 43 days durability and until two months. Finally, it was made the production costs for the best treatment with tzintzo extract microencapsulation